Square peg in a round hole: are small private liberal arts higher education institutions prepared to implement lean operational and organizational methodologies to survive?. (2nd January 2022) - Fowler, David S.
ABSTRACT: The focus of this paper is to promote the awareness of higher-education administration and faculty of the opportunities presented by developing and implementing lean operational models in their institutions. The paper provides a brief account of the author's observations of small liberal arts colleges that are operating in non-efficient models. It also provides an insight into the author's experience with orchestrating organisational change which included multiple transformational projects over a significant period of years in corporate America. It also provides the reader with published information suggesting that lean implementation, while difficult to sell, makes sense in the small liberal arts' higher education environment. The first finding is that many of these institutions are failing and not operating efficiently. Second, lean operational methodologies being deployed by many higher education entities, are successful. Third, operational and organisational change is difficult to sell within a very tradition-based environment, however, it is possibly a necessity to implement for survival. There is a significant opportunity for educational leaders to consider the implementation of lean operational models to promote the success of their organisations. Failure to achieve operational success may cause significant disruption to or even failure of small private liberal arts schools. Efficiently providing quality education is good for future generations by providing venues for potential success, and that is advantageous for society. Research exists considering lean operational methodologies in higher education. However, there is a lack of literature available focusing on the specifics of small private liberal arts colleges, their dilemmas, and their needs. There is a need for these schools to survive, so educational leaders should contemplate these suggestions.